Early strength permeable crystallization grouting material for filling voids in operating tunnel lining and preparation method of grouting slurry
By using early-strength permeable crystalline grouting materials in tunnel lining holes, the problems of large and poor water consumption and poor stability of traditional grouting materials are solved, high early strength and excellent waterproofing effects are achieved, and the stability and operational safety of the tunnel structure are improved. .
Patent Information
- Application Number
- CN202211686426.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-27
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-12-27
AI Technical Summary
Traditional tunnel lining hollow treatment grouting materials have large water consumption, poor stability and low early strength, resulting in unstable tunnel structure, increasing self-weight and affecting operational safety.
Use early-strength permeability crystalline grouting materials, including ultrafine silicate cement, fast hardener, vapor phase silica, water reducing agent, stabilizer, plastic expansion agent, compensation shrink expansion agent, retarder, and defoaming agent and permeable crystallizer are prepared by specific ratios and stirring methods to form a high-flow, slightly expanded grouting slurry, filling the voids and providing excellent waterproofing effect.
It has achieved high early strength and good permeability crystallization waterproofing effect, met the construction requirements of the skylight period of the operating tunnel, improved the stability and operation safety of the lining structure, and effectively curated the concrete water leakage problem.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of construction and geotechnical engineering, and in particular to an early-strength permeable crystallization grouting material for filling cavities in an operating tunnel lining and a preparation method of a grouting slurry. Background Art
[0002] At present, my country's railway transportation industry has developed rapidly, and an efficient, safe, convenient and green integrated transportation system has been basically established. With the increase in the number of operating tunnels, some tunnels have suffered from varying degrees of defects due to the influence of geological conditions, geological structure and groundwater conditions as well as the construction factors at the time, such as tunnel lining debonding, structural water leakage, etc., which seriously affected the safety of railway operations.
[0003] The grouting materials for treating the voids in traditional tunnel linings are mostly cement slurry or cement-water glass double slurry, and the voided area is backfilled and grouted by low-pressure grouting. This type of material consumes a large amount of water, has poor slurry stability, severe water seepage and stratification, large shrinkage rate after slurry solidification, and low early strength, which cannot meet the construction requirements of the skylight period of operating tunnels. The results of on-site core sampling and testing showed that the traditional grouting materials after solidification and hardening were separated from the lining concrete and the upper waterproof board, forming a "two-layer skin" phenomenon on the tunnel lining structure, which not only failed to improve the stability of the lining structure, but increased the deadweight of the lining, which had an adverse effect on the stability of the tunnel lining structure and operational safety. Summary of the invention
[0004] In order to solve the defects of the prior art, the present invention proposes an early-strength permeable crystallization grouting material for filling the lining voids of an operating tunnel and a preparation method of the grouting slurry. The material has ultrafine, high fluidity, micro-expansion, good void filling properties, and can fill tiny cracks. It has high early strength and excellent permeable crystallization waterproofing effect, which meets the construction requirements for filling and repairing the lining voids during the skylight period of the operating tunnel, and at the same time has a good treatment effect on the leakage of lining concrete.
[0005] In the first aspect, the technical solution adopted by the present invention is an early-strength penetrating crystallization grouting material for filling voids in operating tunnel linings, comprising the following components in parts by weight: 650-850 parts of silicate cement; 100-200 parts of quick-hardening agent; 5-10 parts of fumed silica; 3-6 parts of water reducer; 0.2-0.5 parts of stabilizer; 0.2-0.5 parts of plastic expansion agent; 50-100 parts of compensating shrinkage expansion agent; 0.2-1 parts of retarder; 0.3-0.8 parts of defoaming agent; and 5-15 parts of penetrating crystallization agent.
[0006] Preferably, the silicate cement is ultrafine silicate cement, with D90≤20 μm and strength grade of 52.5.
[0007] Preferably, the quick-hardening agent is beform quick-hardening agent produced by Nippon Denki Chemical.
[0008] Preferably, the fumed silica is nano-scale amorphous silica with a specific surface area greater than 200 m2 / g and an average particle size less than 30 nm.
[0009] Preferably, the water reducer is a powdered polycarboxylic acid high-performance water reducer, and the stabilizer is modified magnesium aluminum silicate.
[0010] Preferably, the plastic expansion agent is azodicarbonamide, and the compensating shrinkage expansion agent is calcium sulfoaluminate expansion agent UEA.
[0011] Preferably, the retarder is L-tartaric acid, and the defoamer is a polyether-modified polysiloxane defoamer.
[0012] Preferably, the osmotic crystallization agent is a mixture of quick-dissolving sodium silicate and aluminum stearate in a weight ratio of 1:1.
[0013] In the second aspect, the present invention also proposes a method for preparing a grouting slurry, characterized in that the method comprises: obtaining corresponding components according to the ratio of the aforementioned early-strength penetrating crystallization grouting material for filling voids in the operating tunnel lining and mixing them evenly to obtain the grouting material; adding the grouting material into water and continuously stirring during the adding process to obtain a grouting slurry; wherein the stirring time is 3-5 minutes, and the weight ratio of the grouting material to water is 1:(0.25-0.27).
[0014] Preferably, the obtaining of the corresponding components and mixing them evenly to obtain the grouting material is specifically: placing the corresponding components into a zero-gravity mortar mixer and mixing them evenly to obtain the grouting material.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] 1. The material has ultra-fine, high fluidity, micro-expansion, good void filling, and can fill tiny cracks;
[0017] 2. It has high early strength and excellent penetration crystallization waterproofing effect, which can meet the requirements of lining void filling and repair construction during the skylight period of operating tunnels, and at the same time has a good control effect on lining concrete leakage. DETAILED DESCRIPTION
[0018] Example 1, an early-strength penetrating crystallization grouting material for filling voids in operating tunnel linings, comprising the following components in parts by weight: 800 parts of ultrafine silicate cement; 130 parts of fast-hardening agent; 7 parts of fumed silica; 4 parts of powdered polycarboxylic acid water-reducing agent; 0.5 parts of modified magnesium aluminum silicate; 0.3 parts of azodicarbonamide; 50 parts of UEA expansion agent; 0.6 parts of L-tartaric acid; 0.8 parts of organosilicon defoaming agent; 10 parts of penetrating crystallization agent (composed of 5 parts of instant sodium silicate and 5 parts of aluminum stearate).
[0019] The above material components are placed in a zero-gravity mortar mixer and stirred evenly to obtain the grouting material.
[0020] Example 2, an early-strength penetrating crystallization grouting material for filling voids in operating tunnel linings, comprising the following components in parts by weight: 770 parts of ultrafine silicate cement; 120 parts of fast-hardening agent; 5 parts of fumed silica; 3.5 parts of powdered polycarboxylic acid water-reducing agent; 0.4 parts of modified magnesium aluminum silicate; 0.4 parts of azodicarbonamide; 80 parts of UEA expansion agent; 0.5 parts of L-tartaric acid; 0.7 parts of silicone defoaming agent; 15 parts of penetrating crystallization agent (composed of 7.5 parts of instant sodium silicate and 7.5 parts of aluminum stearate).
[0021] The above material components are placed in a zero-gravity mortar mixer and stirred evenly to obtain the grouting material.
[0022] Example 3, an early-strength penetrating crystallization grouting material for filling voids in operating tunnel linings, comprising the following components in parts by weight: 700 parts of ultrafine silicate cement; 180 parts of fast-hardening agent; 10 parts of fumed silica; 6 parts of powdered polycarboxylic acid water-reducing agent; 0.2 parts of modified magnesium aluminum silicate; 0.5 parts of azodicarbonamide; 100 UEA expansion agent; 1 part of L-tartaric acid; 0.4 parts of organosilicon defoaming agent; 5 parts of penetrating crystallization agent (composed of 2.5 parts of instant sodium silicate and 2.5 parts of aluminum stearate).
[0023] The above material components are placed in a zero-gravity mortar mixer and stirred evenly to obtain the grouting material.
[0024] It should be noted that the early-strength penetrating crystallization grouting material used for filling the lining voids of the operating tunnel in the above-mentioned multiple embodiments, ultrafine silicate cement and rapid hardening agent as the main body of the composite gel system, are prepared in a certain proportion, and nano-grade fumed silica, specific functional additives, penetrating crystallization components, etc. are added. The obtained grouting material is ultrafine, highly fluid, slightly expanded, has good void filling properties, and can fill tiny cracks. It has high early strength and excellent penetrating crystallization waterproofing effect, which meets the requirements of the lining void filling and repair construction during the skylight period of the operating tunnel, and at the same time has a good treatment effect on the leakage of lining concrete.
[0025] Among them, the silicate cement is ultrafine silicate cement, and its D90≤20μm, and the strength grade is 52.5; the meaning of D90 here refers to: the particle size corresponding to when the cumulative particle size distribution number of the cement sample reaches 90%, and the physical meaning embodied in the above embodiment is that the particles of the cement with a particle size of less than 20μm account for 90% of the total particles. Since the particle size of ultrafine silicate cement is only a fraction of that of ordinary cement, it has excellent pourability and can be poured into tiny cracks and fissures of concrete and surrounding rocks. The composite system of rapid hardening agent and silicate cement can increase the early 2h strength to more than 10MPa through a specific proportion, and the later strength does not shrink or decrease. It avoids the problem of later strength reduction caused by the combination of early strength agent + silicate cement. And the rapid hardening agent reacts with silicate cement to generate a large amount of calcium sulfonate, which helps to reduce the volume shrinkage of the slurry after hardening.
[0026] Among them, the combination of plastic expansion agent-azodicarbonamide and compensating shrinkage expansion agent-UEA expansion agent can achieve micro-expansion of the slurry in the plastic stage and reduce the shrinkage in the later stage, making the grouting material more densely filled and avoiding cracks and voids caused by slurry volume shrinkage.
[0027] Among them, the combined use of stabilizer and water reducer can ensure that the grouting material is in a high fluid state without segregation, water seepage and stratification, thereby improving the stability of the slurry, reducing the degree of separation, ensuring the uniform and stable quality of the grouting material, and facilitating the combination of the grouting material with the old concrete, thereby improving the grouting density.
[0028] The fumed silica is amorphous nano-scale silica. Since the fumed silica is nano-scale, the average particle size is less than 30nm, the surface area is greater than 200㎡ / g, and it has very high surface activity. It can react with the cement hydration product Ca(OH)2 to form CSH gel, thereby improving the hardening strength of the slurry. In addition, its particle size is nano-scale and its specific surface area is large, which can effectively fill the fine pores and weak base surfaces in the hardened cement slurry, increase the density of the hardened slurry, reduce the porosity, reduce internal defects, improve the hardening strength and impermeability of the cement, and reduce the shrinkage rate.
[0029] Among them, the penetrating crystallizer is a new rigid waterproof component that can achieve penetrating crystallization effect. It is mainly composed of fast-soluble sodium silicate and aluminum stearate, and contains a variety of active chemical substances, which can significantly improve the waterproofness and impermeability of the grouting material itself. When cracks and water seepage appear in the tunnel lining, the penetrating crystallization active chemical substances in the grouting material will penetrate into the concrete cracks after reacting with water, forming water-insoluble crystals in the concrete to fill the capillary channels and cracks, thereby making the concrete cracks self-healing and dense, improving waterproofness and anti-seepage.
[0030] The organic silicon defoamer used is a polyether modified polysiloxane defoamer; the quick hardening agent is beform from Nippon Denki Kagaku Co., Ltd., a calcium aluminate type; the water reducing agent is a powdered polycarboxylic acid high-performance water reducing agent; and the organic silicon defoamer is a polyether modified polysiloxane defoamer.
[0031] The present invention also discloses a method for preparing a grouting slurry, the method comprising: obtaining corresponding components according to the above-mentioned proportions; putting each component into a weightless mortar mixer and mixing them evenly, so as to obtain an early-strength penetrating crystallization grouting material for filling voids in an operating tunnel lining; adding the grouting material into water, and continuously stirring during the adding process to obtain a grouting slurry. Among them, the grouting material is prepared and stirred into a slurry according to a material-water ratio of 1:0.26 (or 1:0.25, 1:0.27) during actual use, and the order of adding materials when preparing the slurry is: first add water, then add the grouting material, stir while adding the grouting material, until a uniform slurry is generated, and then grouting is performed. The stirring equipment should be a high-speed mixer, the rotation speed of which is not less than 600r / min, and the stirring time is 3-5min.
[0032] Cement slurry
[0033] Traditional cement slurry preparation materials and processes use Lafarge PO42.5 ordinary Portland cement with a water-to-cement ratio of 0.75, which is stirred to generate a uniform slurry.
[0034] Comparative Example
[0035] The finished product of cement-based grouting material for filling a tunnel cavity is mainly composed of cement and various functional additives, with a water-to-cement ratio of 0.30, which is stirred to form a uniform slurry.
[0036] The slurries and cement slurries prepared in Examples 1-3 and the slurries prepared in the comparative examples were tested for slurry workability, stability, expansion rate, strength, waterproofness and anti-seepage, etc. The testing methods can be based on conventional quality inspection methods in the prior art. The test results are shown in Table 1 below.
[0037] Table 1 Properties of grouting materials
[0038]
[0039] As can be seen from Table 1, the slurry prepared by the grouting materials of Examples 1-3 of the present invention has good fluidity, stable slurry, no stratification, no water seepage, slight volume expansion in the plastic stage, and low shrinkage rate in the later stage. And the anti-seepage pressure is excellent, all above 2.0MPa. The early 2h compressive strength is greater than 10MPa, which meets the construction requirements of the skylight period of the operating tunnel. Compared with Examples 1-3 of the present invention, the traditional cement slurry and the comparative example have poor slurry fluidity and stability, are prone to water seepage and stratification, and the ordinary cement slurry has a large early and late shrinkage rate, low early strength, and has not solidified for 2h, so it cannot meet the construction requirements of the skylight period of the operating tunnel. And the 28d anti-seepage pressure of the traditional cement slurry and the comparative example is relatively low, which cannot meet the waterproof and water-stopping requirements of the tunnel lining.
[0040] In the description of this specification, if the terms "embodiment one", "this embodiment", "in an embodiment" and the like appear, it means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in the invention or at least one embodiment or example of the invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example; moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in an appropriate manner.
[0041] In the description of this specification, the terms "connect", "install", "fix", "set", "have", etc. are all understood in a broad sense. For example, "connection" can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be an indirect connection through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0042] In the description of this specification, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "comprises", "comprising" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the statement "comprising a ..." does not exclude the presence of other identical elements in the process, method, article or device including the element.
[0043] The above description of the embodiments is to facilitate ordinary technicians in the technical field to understand and apply the technology of this case. People familiar with the technology in this field can obviously easily make various modifications to these examples and apply the general principles described here to other embodiments without creative work. Therefore, this case is not limited to the above embodiments. Modifications to the following situations should all be within the scope of protection of this case: ① A new technical solution implemented based on the technical solution of the present invention and combined with existing common knowledge, the technical effect produced by the new technical solution does not exceed the technical effect of the present invention; ② The equivalent replacement of some features of the technical solution of the present invention by using known technology, the technical effect produced is the same as the technical effect of the present invention; ③ The technical solution of the present invention can be expanded, and the substantive content of the expanded technical solution does not exceed the technical solution of the present invention; ④ The equivalent transformation made by using the content of the specification of the present invention is directly or indirectly applied to other related technical fields.
Claims
1. Early strength permeable crystallization grouting material for filling voids in operating tunnel lining, characterized in that: The invention comprises the following components in parts by weight: 650-850 parts of silicate cement; 100-200 parts of quick-hardening agent; 5-10 parts of fumed silica; 3-6 parts of water reducing agent; 0.2-0.5 parts of stabilizer; 0.2-0.5 parts of plastic expansion agent; 50-100 parts of compensating shrinkage and expansion agent; 0.2-1 parts of retarder; 0.3-0.8 parts of defoaming agent; 5-15 parts of penetrating crystallization agent; The plastic expansion agent is azodicarbonamide, the compensating shrinkage expansion agent is calcium sulfoaluminate expansion agent UEA; the infiltration crystallization agent is a mixture of quick-dissolving sodium silicate and aluminum stearate in a weight ratio of 1:1; the silicate cement is ultrafine silicate cement, with D90≤20μm and strength grade of 52.5; the fumed silica is nano-scale amorphous silica with a specific surface area of 200m 2 / g, average particle size <30nm.
2. The early-strength permeable crystallization grouting material for filling voids in operating tunnel linings according to claim 1 is characterized in that: The quick-hardening agent is beform quick-hardening agent produced by Japan Electric Chemical.
3. The early-strength permeable crystallization grouting material for filling voids in operating tunnel linings according to claim 1 or 2, characterized in that: The water reducer is a powdered polycarboxylic acid high-performance water reducer, and the stabilizer is modified magnesium aluminum silicate.
4. The early-strength permeable crystallization grouting material for filling voids in operating tunnel linings according to claim 3 is characterized in that: The retarder is L-tartaric acid, and the defoamer is a polyether-modified polysiloxane defoamer.
5. A method for preparing a grouting slurry, characterized in that: The method comprises: obtaining corresponding components according to the proportion of the early-strength penetrating crystallization grouting material for filling voids in an operating tunnel lining as described in any one of claims 1 to 4 and mixing them evenly to obtain the grouting material; adding the grouting material into water and continuously stirring during the adding process to obtain a grouting slurry; wherein the stirring time is 3 to 5 minutes, and the weight ratio of the grouting material to water is 1:(0.25-0.27).
6. The method for preparing the grouting slurry according to claim 5, characterized in that: The step of obtaining the corresponding components and mixing them evenly to obtain the grouting material is specifically as follows: putting the corresponding components into a zero-gravity mortar mixer and mixing them evenly to obtain the grouting material.
